Does a personalized feedback on investment success mitigate investment mistakes of private investors? Answers from large natural field experiment - Steffen Meyer; Linda Urban; Sophie Ahlswede (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this natural field experiment with almost 2.000 customers of an online-broker we test what happens when investors receive feedback on their investment success in a monthly securities account report. We test four designs using different graphical displays and text. All report designs show investors last year s returns, costs, their current level of risk and their portfolio diversification. Depending on the design, we also include peer-group and/or benchmark information. Over a period of six months, we find that the reports induce an increase in trading activity, a deterioration in diversification measures, and reduces stock market exposure. Results are robust to controlling for potential play money accounts and changes in report designs. The results imply that feedback may be a necessary, but not a sufficient condition for helping retail investors making better investment decisions.
Keywords: D14; H11; G28; 330